Informe del proyecto de vinculación “Optimizando emprendimientos y organizaciones sociales” desarrollado durante el semestre 2020-1 en alianza con la Agencia de Promoción Económica ConQuito - De La Torre Contrera, Cristina Alejandra (2020)
This document is a compilation of the work carried out during the linking Project Optimizing social enterprises and organizations. This project was carried out by students from the Universidad de Las Américas from a strategic alliance between the Conquito Economic Promotion Agency and the academy. The work team was made up of 2 teachers in charge of the project, 2 Industrial Engineering subjects and approximately 60, who carried out the study and application of improvement tools in 14 enterprises that are part of Conquito and are located in the metropolitan district of Quito. As a first point, an analysis of the initial state of the enterprises was carried out, through the SWOT analysis, which will diagnose and direct its strategic plan in the market. An analysis of the implementation of improvement tools in each undertaking was also carried out, which includes the times for preparing the products, the production or service processes, their resources, materials and personnel responsible for each activity in the process. As part of the results, an analysis of the audits carried out before and after the application of the 5s methodology was carried out, a comparative table is also made that allows understanding the percentage of optimization achieved through the mentioned methodology. As a compilation of the results, a matrix analyzed the improvements achieved by each tool in the undertakings, according to the production or service sector to which they belong. With these values, an optimization matrix of times and movements was made based on the improvement proposal established by the, specifying the percentage of optimization of the students and required production or service times. Finally, bonding experiences are analyzed from the point of view of each participant in the project and their contribution to the development of students in a real environment.